2015
DOI: 10.1021/acs.jpcc.5b05070
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Nature of Formate Species in the Decomposition and Reaction of Methanol over Cerium Oxide Surfaces: A Combined Infrared Spectroscopy and Density Functional Theory Study

Abstract: Formation of formate species on oxide surfaces plays a role in reactions for hydrogen production such as the water-gas shift, and the steam reforming of alcohols. It has been suggested that bridge formates are the most common and stable configuration on metal oxides. Ceria-based catalysts are important for these reactions where ceria is a "noninnocent" support. In this work, the nature of the formate species that are formed during decomposition and reaction of methanol on ceria surfaces have been studied using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 70 publications
(114 reference statements)
5
52
0
Order By: Relevance
“…The previously calculated barriers for the formation of acetaldehyde through HC scission from the LD and SU ethoxy species on the CeO 2 (111) surface [48], provide support to our proposal, since a larger energy barrier was found for the formation of acetaldehyde through -HC scission in the case of the LD species (2.08 eV) as compared to the barrier for the process through -HC scission in the case of the SU ethoxy species (1.11 eV). It is important to note that the here reported theoretical calculations predict OH groups to have a decisive impact on the adsorbed ethoxy species (see Supporting Information), similar as previously reported for formate on ceria [49].…”
Section: Adsorption Of Ethanol On Ceo 2 and Cegao Xsupporting
confidence: 86%
“…The previously calculated barriers for the formation of acetaldehyde through HC scission from the LD and SU ethoxy species on the CeO 2 (111) surface [48], provide support to our proposal, since a larger energy barrier was found for the formation of acetaldehyde through -HC scission in the case of the LD species (2.08 eV) as compared to the barrier for the process through -HC scission in the case of the SU ethoxy species (1.11 eV). It is important to note that the here reported theoretical calculations predict OH groups to have a decisive impact on the adsorbed ethoxy species (see Supporting Information), similar as previously reported for formate on ceria [49].…”
Section: Adsorption Of Ethanol On Ceo 2 and Cegao Xsupporting
confidence: 86%
“…After methanol adsorption (CH 3 OH/He, 100 °C) on the reference ceria sample (Fig. 4a, b), the spectrum shows bands at 2942, 2911, 2888 and 2840 cm − 1 (ν C-H), attributed to the stretching vibrations of the surface methoxy -OCH 3 groups [50][51][52][53]. At the lower frequency range, their bending equivalents are the bands at 1463, 1371, 1355, 1103 and 1056 cm − 1 .…”
Section: Methanol Adsorptionmentioning
confidence: 99%
“…52 As for the WGS reaction, it is reported that the high oxygen storage capacity is beneficial to the catalyst activity as the oxygen could operate in a redox mode. [53][54][55][56] Table 2 shows the quantitative analysis of oxygen species in the reduced catalysts. The amount of lattice oxygen per surface area increases with an increasing amount of CeO 2 because the CeO 2 is known to have an oxygen storage capacity.…”
Section: Reduction Profile (Tpr) Of Fresh Catalystsmentioning
confidence: 99%